SELF ASSESMENT SISTEM SEBAGAI DASAR PUNGUTAN PAJAK DI INDONESIA (Analisa Hukum Tentang Ketentuan Umum Dan Tata Cara Perpajakan) - Imron Rizki A (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
The applicable tax collection system in Indonesia has changes, starting from the system assessment official, then semi-self system assessment, withholding system and the last is self-assessment system. In this self-assessment system, Taxpayers are given to calculate their own payable tax, deposit and report it to the tax office where they are registered. The application of self-assessment system, as the basis for tax collection in Indonesia has not been fully able to change taxpayers to carry out their taxation activities independently and honestly. The trust given by the laws to taxpayers with a self-assessment system is not accompanied by good legal awareness. The high number of violations by taxpayers caused by the supervision not optimal and the penalties also not maximal.